Management control systems and performance: the mediating role of organisational capabilities in Malaysia - Ong, Tze San; Haghshenas, Zohreh; Teh, Boon Heng; Adedeji, Babatunji Samuel; Magsi, Hussain Bakhsh (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study focuses on the interactive use of Management Control System (MCS) and the identification of threats and opportunities that enables management to respond quickly to changes in the environment. The study aims to examine, from a resource-based view (RBV) perspective, the relationship between interactive use of MCS and organisational capabilities (market responsiveness, strategic networking, process reliability and efficiency, innovativeness and learning) as well as their subsequent impact on organisational performance. An empirical study was conducted involving 70 public-listed companies in Malaysia. The analysis included the use of descriptive and multiple regression tests. The findings provide empirical evidence that interactive MCS facilitates the development of organisational capabilities and that organisational capabilities play a mediating role in the relationship between MCS interactive usage and organisational performance. This study indicates that companies in Malaysia still focus on financial measures rather than on non-financial ones in most of their decision making. Managers who are short-term focused or financially oriented in their decision making may jeopardise the long-term sustainability of their organisations’ performance.